Oral Endothelium Corneum Gigeriae Galli Therapy for Pancreatic Duct Stones: A Prospective Cohort Study - Cao, Dujuan; Li, Huiyu; Wang, Jinxi; Zhang, Fang; Zhao, Haoliang; Ren, Chongren (Turkish Journal of Gastroenterology, 2022)
Background: Pancreatic duct stones obstruct the pancreatic ducts and aggravate clinical symptoms of chronic pancreatitis. Only isolated case reports have shown that some drugs may be useful in dissolving pancreatic duct stones. Endothelium corneum gigeriae galli is a Chinese medicine widely used to cure multifarious lithiasis and maldigestion. This study aimed to evaluate the efficacy of endothelium corneum gigeriae galli oral therapy in the dissolution of stones and evaluate the improvement of clinical symptoms in patients with pancreatic duct stones. Methods: Sixty-eight patients with pancreatic duct stones were randomly divided into the endothelium corneum gigeriae galli and control groups. Endothelium corneum gigeriae galli was given orally to the endothelium corneum gigeriae galli group, and the placebo was given to the control group. Both groups were reviewed by computed tomography and magnetic resonance imaging; abdominal pain, exocrine and endocrine pancreatic function, and the nutritional status of patients were measured after the study. Results: The dissolution rate of the endothelium corneum gigeriae galli group was significantly higher than that of the control group (P = .002). The abdominal pain of the endothelium corneum gigeriae galli group was relieved more significantly compared to that of the control group (P < .001). The exocrine and endocrine pancreatic function of the endothelium corneum gigeriae galli group improved more significantly than that of the control group (P < .001). The nutritional status of the endothelium corneum gigeriae galli group was significantly higher than that of the control group (P = .003). Conclusion: Overall, oral endothelium corneum gigeriae galli treatment could dissolve pancreatic duct stones, relieve abdominal pain, improve exocrine and endocrine pancreatic functions, and control the deterioration of nutritional status. Endothelium corneum gigeriae galli treatment should be useful in pancreatic duct stones therapy. Cite this article as: Cao D, Li H, Wang J, Zhang F, Zhao H, Ren C. Oral endothelium corneum gigeriae galli therapy for pancreatic duct stones: A prospective cohort study. Turk J Gastroenterol. 2022;33(12):1050-1057.